Scientism and atheism then and now: the role of science in the Monist and New Atheist writings. Issue 1 (2nd January 2016) - Kaden, Tom; Schmidt-Lux, Thomas
Abstract: We examine how the authors who represent 'New Atheism' refer to science, and we compare these references to how science was viewed in earlier Continental forms of atheism, namely in Ernst Haeckel's writings and his Monist movement. We analyse and compare these references in five key areas: the general reference to science, the use of science as an argument against religion, reference to a scientific mode of knowledge, scientific theories about religion and science as a means of giving meaning to life. While there are many similarities that clearly position New Atheism within the history of scientism, we find that the form of scientism the New Atheists employ owes at least as much to the current state of religious field as to their scientistic predecessors.